Fibroblast growth factor 21 decreases after liver fat reduction via growth hormone augmentation. (December 2017) - Braun, Laurie R.; Feldpausch, Meghan N.; Czerwonka, Natalia; Torriani, Martin; Grinspoon, Steven K.; Stanley, Takara L.
Abstract: Objective: Fibroblast growth factor 21 (FGF21) ameliorates steatohepatitis but is increased in humans with fatty liver, potentially due to compensatory mechanisms and/or FGF21 resistance. Further, animal models suggest that GH increases serum FGF21. Tesamorelin, a growth hormone releasing hormone agonist, reduces liver fat in HIV-infected individuals. The objectives of this study were to investigate changes in FGF21 during tesamorelin treatment, to elucide the interplay between FGF21, GH augmentation, and liver fat reduction in humans. Methods: 50 HIV-infected men and women with increased abdominal adiposity participated in this randomized, placebo-controlled trial of tesamorelin, 2 mg vs. identical placebo daily for six months. Fasting laboratory measures, liver fat by 1 H-magnetic resonance spectroscopy, and visceral adipose tissue (VAT) by computed tomography were obtained. Euglycemic hyperinsulinemic clamp was performed in a randomly selected subset. Results: At baseline, serum log10 FGF21 was significantly associated with log10 liver fat ( r = 0.32, p = 0.03). Log10 FGF21 tended to decrease in the tesamorelin group compared to placebo ( p = 0.06). Among the entire cohort, reductions in FGF21 were significantly associated with reductions in liver fat (ρ = 0.41, p = 0.01), log10 gamma glutamyl tran speptidase (GGT, r = 0.40, p = 0.009), and FIB4 index ( r = 0.37, p = 0.02). Conclusions: In HIV-infected individuals, FGF21 is significantly positively associated with liver fat. FGF21 decreases in association with reductions in liver fat, GGT, and FIB4, suggesting that FGF21 is upregulated in the context of steatosis and steatohepatitis and is reduced when these conditions improve. Moreover, these data suggest that tesamorelin improves liver fat via pathways other than increasing serum FGF21. Trial registration: clinicaltrials.gov NCT01263717 . Highlights: FGF21 is positively associated with liver fat content in HIV-infected individuals Reductions in liver fat achieved with tesamorelin are significantly associated with reductions in FGF21, GGT, and FIB4. These data suggest that FGF21 is upregulated with increased liver fat, and tesamorelin's effect is not mediated via FGF21.